PENGARUH PENGGUNAAN FLY ASH PADA BETON MUTU NORMAL DAN MUTU TINGGI DITINJAU DARI KUAT TEKAN DAN ABSORBSI - Borris Berqa Leovie Haf (Media Teknik Sipil, 2012)
Fly ash was used in K300 quality and K500 concrete. To find out pressure strength andabsorption, there used cube test with 15 cm measurement. Concrete mixture planning used methodof DOE (development of Environmental). In K300 with FAS 0.63, slump 3 cm – 6 cm and in K500with FAS 0,41, slump 8 cm - 12 cm. by fly ash variances 0%, 30% cementious and 30% additivefrom the total weight of cement. The pressure strength test was done when the concrete age was7, 14 and 28 days. Absorption was tested when the concrete age was 28 days.In this research, concrete with strength K300 and strength K500 showed similar reaction in allvariances of concrete mixture. Fly ash as additive was better compared with its role as cementious.Since both tester showed increasing in concrete pressure for 10% from concrete without fly ash.And fly ash as cementious showed decreasing in concrete pressure for 10% from concrete withoutfly ash, where the avarege of pressure in K300 was 362 kg/cm2 for concrete without fly ash, 273kg/cm2 for concrete with 30% cementious and 398 kg/cm2 for concrete with 30% additive. Andfor K500 concrete were 568 kg/cm2 for concrete without fly ash, 443 for concrete with 30%cementious and 628 kg/cm2 for concrete with 30% additive. And absorption in strength K300 was0.384% for concrete without fly ash, 0.379% for concrete with 30% cementious and 0.363% forconcrete with 30% additive. And also in strength K500 with 0.276% for concrete without fly ash,0.274% for concrete with 30% cementious and 0.259% for concrete with 30% additive.Keyword : ly Ash, Absorption, Cementious, Additive